Conceptualising social justice and sociocultural issues within physical education teacher education: international perspectives. (3rd September 2018) - Hill, Joanne; Philpot, Rod; Walton-Fisette, Jennifer L.; Sutherland, Sue; Flemons, Michelle; Ovens, Alan; Phillips, Sharon; Flory, Sara B.
ABSTRACT: Background: Physical education (PE) and physical education teacher education (PETE) have a substantial literature base that advocates for students to develop a critical consciousness, appreciate multiple perspectives, and engage in actions to enhance social justice [Tinning, R. 2016. "Transformative Pedagogies and Physical Education." In The Routledge Handbook of Physical Education Pedagogies, edited by C. Ennis, 281–294. New York: Routledge]. Analysing sociocultural issues, critically reflecting on beliefs, knowledge, biography, and values, and developing a sense of agency to enact change, have been recognised as an integral part of the PETE knowledge base for some time [Fernández-Balboa, J. M. 1997. "Physical Education Teacher Preparation in the Postmodern era: Toward a Critical Pedagogy." In Critical Postmodernism in Human Movement, Physical Education, and Sport, edited by J. M. Fernández-Balboa, 121–138. Albany: State University of New York Press]. However, there remain differences in how social justice itself is conceptualised and enacted. Social justice is aligned heavily with critical and 'post' theories where taking action for justice, democracy, and power is central; but social justice is also found in humanist beliefs in student-centredness and equality and has been co-opted by neoliberal forces that promote individual responsibility. While a lack of consensus is not in itself a problem [Bialystok, L. 2014. "Politics Without "Brainwashing": A Philosophical Defence of Social Justice Education." Curriculum Inquiry 44 (3): 413–440], diverse definitions might contribute to confusion and lead to uncertainty over what and how to teach for social justice. Purpose: In order to work towards greater certainty around concepts of social justice in the PETE community, this project sought to map variations in definition and conceptualisation of social justice and sociocultural issues among physical education teacher educators (PETEs) and physical education and sport pedagogy (PESP) educators, as part of a wider project on social justice and sociocultural perspectives and practices in PETE. Methods: PETE and PESP faculty ( n  = 72) in North America, Europe, and Australasia engaged in an in-depth interview, during which they were asked how they define social justice and sociocultural issues. Additional information about participants' social identity was collected. A constant comparative method of analysing participants' definitions mapped a range of concepts building on the theoretical framework of neoliberal, humanist, critical, and 'post' approaches to social justice. Findings: The data demonstrate that there are a range of understandings about sociocultural issues and social justice. Most commonly, some participants articulated a humanist approach to social justice by encouraging their pre-service teachers (PSTs) to have awareness of equality of opportunity in relation to gender, sexuality, and/or racism. Less prevalent, but strongly stated by those who conceptualised social justice in these terms, was the importance to take action for democracy, empowerment, or critical reflection. The terms diversity and equality, framed in neoliberal and humanist discourses, were most commonly used within the United States (US), while critical pedagogy and alignment with critical and 'post' theories were more prevalent in Australia and New Zealand. Conclusion : Differences exist in the ways social justice is conceptualised in PETE. While this can be attributed to the influence of local issues, it is also reflective of what intellectual tools, such as humanism or critical theory, are available for problematising social issues. The range of non-critical concepts found raises concern that PSTs are not getting the tools to enact social justice or tackle sociocultural issues.